Immunomodulatory efficacy of Cousinia thomsonii C.B. Clarke in ameliorating inflammatory cascade expressions. (10th January 2023) - Dar, Khalid Bashir; Parry, Ruhban Ansar; Bhat, Aashiq Hussain; Beigh, Afaq Hameed; Ahmed, Maroof; Khaja, Umer Majeed; Ganie, Aijaz Hassan; Mir, Manzoor Ahmad; Reshi, Bilal Ahmad; Khan, Ishfaq Shafi; Ganie, Showkat Ahmad
Abstract: Ethnopharmacological relevance: Cousinia thomsonii is traditionally known for treating various diseases including joint pain, swelling, body ache, asthma, dermatitis, cough and arthritis. Aim of the study: This study employs lipopolysaccharide induced inflammatory wistar-rat model to evaluate efficacy of Cousinia thomsonii active-extracts on the expression of crucial inflammatory markers viz. iNOS, PPAR-γ, Rel-A, COX-2 and serum analysis of CRP. Materials and methods: Methanol and aqueous extracts were administered orally at 25, 50, 100 mg/kg doses for 21 days. Serum was collected on 22nd day and rats were sacrificed to extract paw tissues. Dexamethasone (0.5 mg/kg) served as positive control. Immunoblotting and qPCR was used for expression analysis of iNOS, PPAR-γ, Rel-A, COX-2 respectively. ELISA was employed for evaluating CRP levels. Discovery-studio and Auto-Dock-Vina were used to check docking interactions of various identified compounds. Results: Both extracts caused dose-dependent decline in iNOS, Rel-A, COX-2 and CRP levels, while there was a dose-dependent increase in PPAR-γ expression. Methanol extract dominated immunomodulatory potential as compared with the aqueous extract. The results of the GCMS revealed the presence of ten compounds. Some of these compounds include 1-Octacosanol, Ethyl Linoleate, 1-Heptacosanol, 1-Hexadecanol, 1-Dodecanol and Behenic alcohol having strong anti-inflammatory, antimicrobial, anti-acne and anti-viral activities. Molecular Docking scores were calculated between each target protein and selected compounds. The best affinity/interactions were observed between 1-Octacosanol towards iNOS, PPAR-γ, Rel-A, COX-2 and CRP with binding energy of −10.4, −11.1, −8.6, −9.9 and −7.9 (kcal/mol) respectively. These compounds may act as strong inhibitors for iNOS, Rel-A, COX-2 and CRP or as agonists for PPAR-γ; thereby inducing anti-inflammatory/immuno-modulatory activities. Conclusions: The results indicate that Cousinia thomsonii contains therapeutically active compounds and thus could serve as potential therapeutic regimen against diverse inflammatory diseases. Graphical abstract: Image 1 Highlights: Cousinia thomsonii a medicinal herb, is traditionally used for treating joint pain, swelling, body ache, asthma, dermatitis, cough and arthritis. Cousinia thomsonii inhibits inflammation by reducing inflammatory mediators including iNO, COX-2, CRP, Rel-A and showed marked increase in PPAR-γ levels. GCMS revealed the presence of ten compounds in Cousinia thomsonii and some of these compounds include 1-Octacosanol, Ethyl Linoleate, 1-Heptacosanol, 1-Hexadecanol having strong anti-inflammatory activities. Molecular Docking scores showed the best affinity/interactions of 1-Octacosanol towards iNOS, PPAR-γ, Rel-A, COX-2 and CRP.